Exploring Obstetrical Interventions and Stratified Cesarean Section Rates Using the Robson Classification in Tertiary Care Hospitals in the United Arab Emirates - Mahera Abdulrahman; Sara Saad Abdullah; Aminah Fuad Khalil Alaani; Noora Hassan AlAbdool; Fatma Elzahraa Yehia Sherif; Zainab SalahEldin Ahmed; Hiba Issa Al-Rawi; Nawal Mahmood Hubaishi; Muna AbdulRazzaq Tahlak; Frederick R Carrick (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2019)
Abstract Objective The objective of the present study was to explore obstetric management in relation to clinical, maternal and child health outcomes by using the Robson classification system. Methods Data was collected from obstetrics registries in tertiary care hospitals in Dubai, United Arab Emirates (UAE). Results The analysis of > 5,400 deliveries (60% of all the deliveries in 2016) in major maternity hospitals in Dubai showed that groups 5, 8 and 9 of Robson's classification were the largest contributors to the overall cesarean section (CS) rate and accounted for 30% of the total CS rate. The results indicate that labor was spontaneous in 2,221 (45%) of the women and was augmented or induced in almost 1,634 cases (33%). The birth indication rate was of 64% for normal vaginal delivery, of 24% for emergency CS, and of 9% for elective CS.The rate of vaginal birth after cesarean was 261(6%), the rate of external cephalic version was 28 (0.7%), and the rate of induction was 1,168 (21.4%). The prevalence of the overall Cesarean section was 33%; with majority (53.5%) of it being repeated Cesarean section. Conclusion The CS rate in the United Arab Emirates (UAE) is higher than the global average rate and than the average rate in Asia, which highlights the need for more education of pregnant women and of their physicians in order to promote vaginal birth. A proper planning is needed to reduce the number of CSs in nulliparous women in order to prevent repeated CSs in the future. Monitoring both CS rates and outcomes is essential to ensure that policies, practices, and actions for the optimization of the utilization of CS lead to improved maternal and infant outcomes.